Analisis Karakteristik Gaya Belajar Siswa Pada Mata Pelajaran Matematika SDN Sendangmulyo 02 Semarang - Mahmudi, Eva Tri; Ningsih, Widya Kusuma; Nuriafuri, Rafika (Melati Institute, 2024)
This study aims to analyze the characteristics of learning styles of grade 4A students at SDN Sendangmulyo 02 Semarang to describe the tendency of learning styles possessed by grade 4A students at SDN Sendangmulyo 02 Semarang. The type of research used in this research is descriptive quantitative. Based on the results of research that has been conducted in class 4 SDN Sendangmulyo 02 Semarang, data on the learning styles of students are obtained, namely students with a visual learning style of 13 out of 25 total students with a percentage of 52%. Learners with auditory learning styles are 7 out of 25 total learners with a percentage of 15%. And students with kinesthetic learning styles amounted to 5 out of 25 total students with a percentage of 20%. Based on the research conducted, it shows that in class 4A there is a diversity of student learning styles. Through the acquisition of these data it can also be concluded that the majority of grade 4 students have a visual learning style.